Advanced hepatocellular carcinoma with MET-amplified contained excellent response to crizotinib: a case report - Gu, Yangjun; Xiao, Min; Chen, Zhitao; Li, Qiyong (Frontiers in Oncology, 2023)
Introduction Hepatocellular carcinoma (HCC) is one of the most lethal cancers worldwide. Several novel therapeutic strategies have been developed to prolong the survival of patients with advanced HCC. However, therapeutic decision-making biomarkers owing to the extensive heterogeneity of HCC. Next-generation sequencing (NGS) is generally used in treatment decisions to help patients benefit from genome-directed targeting. Case presentation A 56 year-old male with type-B hepatitis for more than 20 years was admitted to our department and underwent laparoscopic left lateral hepatic lobectomy for hepatocellular carcinoma. Unfortunately, the tumor recurred 1 year later. Despite multiple treatments, the tumor continued to progress and invaded the patient’s 5th thoracic vertebras, leading to hypoesthesia and hypokinesia below the nipple line plane 2 years later. NGS revealed MET amplification, and crizotinib, an inhibitor of MET, was recommended. After administration for a month, tumor marker levels decreased, and the tumor shrunk. The patient has remained in remission since that time. Conclusions We report that a patient with high MET amplification benefited from its inhibitor, which was recommended by NGS. This indicates the potential clinical decision support value of NGS and the satisfactory effect of MET inhibitors.